El entorno familiar y su influencia en el control de emociones de niños con autismo leve en las edades de 3 a 5 años de la unidad educativa particular tejar - Patiño Suarez, Carmen Inés (2018)
Actual education is inclusive that is why institutes should receive kids with different kinds of educational requirement and offer a high quality education due to the value that inclusion has in the scholar room. In the work executed daily at “Tejar” institute arise a problematic with kids that have mild autism, given from the sighting of disruptions constantly in the classroom; it could be noticed the lack that children have in the emotional scope, taking into consideration that the learning and teaching process should be given into an harmonic environment………